2012
DOI: 10.1021/ac302751t
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamid/Silver Composite Particles Produced via Microfluidic Photopolymerization for Single Particle-Based SERS Microsensorics

Abstract: A micro-continuous-flow process was applied for the preparation of swellable polyacrylamide particles incorporating silver nanoparticles. These sensor particles are formed from a mixture of a colloidal solution of silver nanoparticles and monomer by a droplet-based procedure with in situ photoinitiation of polymerization and a subsequent silver enforcement in batch. The obtained polymer composite particles show a strong SERS effect. Characteristic Raman signals of aqueous solutions of adenine could be detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 26 publications
1
66
0
Order By: Relevance
“…Here, as the sensing application of these metal/polymer nanoassembly particles, a test SERS measurement of adenine analytes is performed. Intense local electric field within a few nanometers at the surface of Ag nanoparticles can be generated by LSPR which can enhance the Raman scattering cross‐section of molecules . When different concentrations of adenine solution were applied to the polymer/Au/Ag assembly particles, an intense and sharp SERS signal was observed at ≈738 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Here, as the sensing application of these metal/polymer nanoassembly particles, a test SERS measurement of adenine analytes is performed. Intense local electric field within a few nanometers at the surface of Ag nanoparticles can be generated by LSPR which can enhance the Raman scattering cross‐section of molecules . When different concentrations of adenine solution were applied to the polymer/Au/Ag assembly particles, an intense and sharp SERS signal was observed at ≈738 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Particles loaded with different semiconductor or magnetic nanoparticles were produced in this way [21,25,26] . In a recent work [27] , polyacrylamide particles incorporating silver nanoparticles were produced as on-chip probes for microfluidic surface-enhanced Raman spectroscopy (SERS). Finally, the functionalization of polymer particles can also be realized in microfluidic processes, for example, by synthesizing porous particles like molecularly imprinted polymer (MIP) beads, which are used for the trace detection of analytes and for chromatographic purposes [19,28,29] .…”
Section: Polymer Particle Synthesismentioning
confidence: 99%
“…These composite microparticles allow an easy handling of nanoparticles and may find applications in sensorics as the plasmonic properties of encapsulated nanoparticles may be affected by pH, oxygen content, or analyte concentration. Preliminary experiments showed that Ag-nanoparticlesdoped poly(AA) microparticles exhibit a strong surface-enhanced Raman spectroscopy (SERS) signal upon contact with ademine concentration as low as 0.1 μM [26].…”
Section: Controlling Droplets and Microparticlesmentioning
confidence: 99%